Visible-light-driven photocatalytic glycerol oxidation to value-added and highly selective glyceric/lactic acid - Kulkarni-Sambhare, Mukta; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S. (ChemiCatChem, 2025)
Achieving economical and sustainable artificial photosynthesis (APS) in direct sunlight for liquid fuel production with high efficiency remains an important challenge. A major obstacle in the photoelectrochemical (PEC) oxidation of organic compounds is attaining high selectivity with the desired product(s). This study introduces a novel strategy by integrating BiVO4 quantum dots (BVQDs), structurally and electronically, into the nanopores of commercial TiO2 (BVT for BVQDs integrated in pores of TiO2) to improve solar-driven photocatalysis. The band gap of the BVT photoanode decreases to 2.53 eV as compared to pure TiO2 (3.2 eV), which enhances visible light absorption and charge separation. BVT with Pt as a co-catalyst acts as an APS system, which selectively oxidizes glycerol into lactic acid (100% selectivity at 1 mM glycerol) and glyceric acid (98% selectivity at 100 mM), while simultaneously generating green hydrogen. Selectivity of the product can be further controlled by anaerobic or aerobic conditions as well as the length of the reaction time. Direct integration of BVQDs into TiO2 mesopores significantly enhances charge separation as well as utilization at redox sites. Current work provides key insights into optimizing photocatalytic conditions for highly selective value-added chemical production, which highlights the sustainability and efficacy of TiO2-based semiconductors with quantum dot integration.
Keywords: energy conversion; Energy storage; Photocatalysis; Quantum material; solar energy